2003
DOI: 10.1007/s00203-003-0591-y
|View full text |Cite
|
Sign up to set email alerts
|

?-Butyrolactone autoregulators and receptor proteins in non-Streptomyces actinomycetes producing commercially important secondary metabolites

Abstract: The presence of gamma-butyrolactone autoregulators and their receptor proteins were investigated in five representative strains of non- Streptomyces actinomycetes producing commercially important secondary metabolites. Ethyl acetate extracts of culture were assayed using wild-type S. virginiae for virginiae butanolide, S. lavendulae FRI-5 for IM-2, and S. griseus HH1 for A-factor. Actinoplanes teichomyceticus and Amycolatopsis mediterranei were shown to produce autoregulators. Corresponding autoregulator-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…We previously designed a primer set (AF-V and AR-1) for this region and successfully used it to amplify and clone several receptor genes from Streptomyces species (Lee et al 2005) as well as from Kitasatospora setae (Choi et al 2004), a member of non-Streptomyces actinomycetes closely related phylogenetically to the genus Streptomyces. However, all our attempts with this primer set failed to amplify homologues of a receptor gene from more distantly related non-Streptomyces actinomycetes, such as A. mediterranei, although our previous study suggested the presence of a c-butyrolactone autoregulator-dependent system in these non-Streptomyces actinomycetes (Choi et al 2003), suggesting that the sequence for the HTH motif may deviate slightly from those in the Streptomyces autoregulator receptors. Thus, we redesigned degenerate primers (F4 and R1) for the HTH motif based on the sequence of the ksbA gene of K. setae, in which the nucleotides of the forward primer (primer F4) are shorter than those of AF-V and one nucleotide is changed, and the position of the reverse primer (primer R1) moves to the 3 0 -side of the HTH region compared with that of primer AR-1.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously designed a primer set (AF-V and AR-1) for this region and successfully used it to amplify and clone several receptor genes from Streptomyces species (Lee et al 2005) as well as from Kitasatospora setae (Choi et al 2004), a member of non-Streptomyces actinomycetes closely related phylogenetically to the genus Streptomyces. However, all our attempts with this primer set failed to amplify homologues of a receptor gene from more distantly related non-Streptomyces actinomycetes, such as A. mediterranei, although our previous study suggested the presence of a c-butyrolactone autoregulator-dependent system in these non-Streptomyces actinomycetes (Choi et al 2003), suggesting that the sequence for the HTH motif may deviate slightly from those in the Streptomyces autoregulator receptors. Thus, we redesigned degenerate primers (F4 and R1) for the HTH motif based on the sequence of the ksbA gene of K. setae, in which the nucleotides of the forward primer (primer F4) are shorter than those of AF-V and one nucleotide is changed, and the position of the reverse primer (primer R1) moves to the 3 0 -side of the HTH region compared with that of primer AR-1.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, numerous regulatory cascades have been found in the genus Streptomyces, whereas there are only a few reports of them in closely related genera, including the so-called non-Streptomyces actinomycetes, which also provide a variety of medically and commercially important secondary metabolites. We previously proposed the possibility of a c-butyrolactone-autoregulator-mediated system in non-Streptomyces actinomycetes, such as Kitasatospora setae, Actinoplanes teichomyceticus, Micromonospora echinospora and Amycolatopsis mediterranei (Choi et al 2003), and demonstrated that KsbA from K. setae is an autoregulator receptor acting as a negative regulator on the biosynthesis of secondary metabolites (Choi et al 2004). However, from the phylogenetic viewpoint, the genus Kitasatospora is very closely related to the genus Streptomyces, whereas the genera Actinoplanes, Micromonospora and Amycolatopsis are more distantly related to Streptomyces.…”
Section: Introductionmentioning
confidence: 98%
“…We have previously reported that ␥-butyrolactone autoregulators and/or the receptor proteins were present in several non-Streptomyces actinomycetes (Kitasatospora setae IFO14216, Actinoplanes teichomyceticus IFO13999, Amycolatopsis mediterranei IFO13415, and Micromonospora echinospora IFO13250) (3,4). In the present study, a ␥-butyrolactone autoregulator receptor gene of K. setae was cloned for the first time from the genera of non-Streptomyces actinomycetes.…”
mentioning
confidence: 77%
“…39 These quorumdependent autoregulators, analogous to the homoserine lactones of some Gram-negative bacteria, 40 have been implicated in regulation of secondary metabolism and cellular differentiation in a number of actinomycetes. 41,42 …”
Section: Structures and Biosynthesismentioning
confidence: 99%